2010
DOI: 10.1177/0022034510383691
|View full text |Cite
|
Sign up to set email alerts
|

Novel Molecular Events in Oral Carcinogenesis via Integrative Approaches

Abstract: Cancer is now viewed as a systems biology disease, and oral squamous cell carcinoma (OSCC) can be viewed in a similar fashion. In this paper, we highlight some of the novel molecular events in OSCC, revealed through an integrative strategy of systems biology based on high-throughput omics analysis such as genomics and/or proteomics, the most powerful hypothesis-generating means available today. These approaches have resulted not only in the identification of novel genes for OSCC, but also in more comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 92 publications
0
15
0
2
Order By: Relevance
“…Studies on animal disease models such as colitis and IBD illustrate an altered pathological status of the immune system. In addition, in the oral mucosa, ECs and immune cells produce a wide range of cytokines, including IL-1β, IL-6, TNF-α, granulocyte-monocyte colony-stimulating factor and TGF-β, 65,84,98 which contribute to an environment that impacts T cell activation, proliferation and differentiation. However, much work is required for a clear understanding of T cell subsets and their function in the oral pharyngeal immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on animal disease models such as colitis and IBD illustrate an altered pathological status of the immune system. In addition, in the oral mucosa, ECs and immune cells produce a wide range of cytokines, including IL-1β, IL-6, TNF-α, granulocyte-monocyte colony-stimulating factor and TGF-β, 65,84,98 which contribute to an environment that impacts T cell activation, proliferation and differentiation. However, much work is required for a clear understanding of T cell subsets and their function in the oral pharyngeal immune system.…”
Section: Discussionmentioning
confidence: 99%
“…82,83 OLP, a chronic inflammatory disease, is characterized by massive lymphocyte infiltration in the LP and results in chronic destruction of the epithelium basal layer. 84,85,86 Scully et al . 75,85,87,88 suggested that T H 1 and T H 2 cells contribute to inflammation and mucosal lesion formation in OLP.…”
Section: T Cell Subsets and Functions In Mucosal Immunitymentioning
confidence: 99%
“…Oral carcinogenesis is a multistep process of cumulative genetic and epigenetic aberrations affecting key signalling pathways, allowing cells to establish a transformed phenotype 21 22. Phosphorylation of p120 has been shown to correlate with cell transformation, and p120 phosphorylation at Y228 is a potent downstream effector of EGFR activation 11 15.…”
Section: Discussionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is a highly variable disease with multiple heterogeneous genetic and epigenetic changes that accounts for ~90% of malignant oral lesions (1). Despite the improvement in OSCC treatments, the overall survival of patients has not improved significantly during the past 20 years, with 5-year survival rates of 45–60% (2,3).…”
Section: Introductionmentioning
confidence: 99%